Perceptual Learning Improves Stereoacuity in Amblyopia - Xi, Jie (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. Amblyopia is a developmental disorder that results in both monocular and binocular deficits. Although traditional treatment in clinical practice (i.e., refractive correction, or occlusion by patching and penalization of the fellow eye) is effective in restoring monocular visual acuity, there is little information on how binocular function, especially stereopsis, responds to traditional amblyopia treatment. We aim to evaluate the effects of perceptual learning on stereopsis in observers with amblyopia in the current study. METHODS. Eleven observers (21.1 ± 5.1 years, six females) with anisometropic or ametropic amblyopia were trained to judge depth in 10 to 13 sessions. Red–green glasses were used to present three different texture anaglyphs with different disparities but a fixed exposure duration. Stereoacuity was assessed with the Fly Stereo Acuity Test and visual acuity was assessed with the Chinese Tumbling E Chart before and after training. RESULTS. Averaged across observers, training significantly reduced disparity threshold from 776.7″ to 490.4″ (P < 0.01) and improved stereoacuity from 200.3″ to 81.6″ (P < 0.01). Interestingly, visual acuity also significantly improved from 0.44 to 0.35 logMAR (approximately 0.9 lines, P < 0.05) in the amblyopic eye after training. Moreover, the learning effects in two of the three retested observers were largely retained over a 5-month period. CONCLUSIONS. Perceptual learning is effective in improving stereo vision in observers with amblyopia. These results, together with previous evidence, suggest that structured monocular and binocular training might be necessary to fully recover degraded visual functions in amblyopia. Chinese Abstract